(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Architectural education in Nigeria faces the challenge of aligning with global sustainability imperatives while addressing local socio-environmental contexts. This study explores innovative pedagogical approaches to integrating sustainability and green design principles within architectural education in Cross River State, Nigeria. Utilizing a mixed-methods approach, primary data were collected through questionnaires and semi-structured interviews with 150 participants, including students, educators, and practicing architects. The findings reveal a high awareness of sustainability (78.6%) but limited practical application due to outdated curricula, insufficient faculty training, and resource constraints. Innovative strategies, such as experiential learning, community-led design studios, and integration of African architectural traditions, were identified as effective in fostering sustainable design thinking. Demographic analysis indicates a youthful participant pool (68% aged 18–30), with a gender distribution of 62% male and 38% female, reflecting the region’s educational trends. The study proposes a framework for curriculum reform, emphasizing interdisciplinary collaboration, digital tools like Building Information Modeling (BIM), and context-driven sustainability studios. These findings contribute to the discourse on sustainable architectural pedagogy in developing nations, offering actionable recommendations for educators and policymakers.